MICROBIALLY CATALYZED DISSOLUTION OF IRON AND ALUMINUM OXYHYDROXIDE MINERAL SURFACE COATINGS - Grantham M.C.; Dove P.M.; DiChristina T.J. (My University, 1997)
This experimental study investigated the processes by which microbes interact with oxyhydroxide mineral surface coatings using an approach designed to better represent the conditions of natural subsurface environments. The interactions of Shewanella putrefaciens, a facultative anaerobe capable of dissimilatory iron reduction, with coatings of Fe3+ and Al3+ oxyhydroxides on natural quartz and silica glass surfaces were examined. Using synthetic groundwater solutions having compositions that simulated a typical aquifer, bacteria were seeded onto mineral surfaces (and coatings) and incubated in parallel with abiotic controls for up to 96 h under aerobic and anaerobic conditions. Microbial-mineral surface interactions were determined using the direct observational technique, Fluid Tapping Mode# Atomic Force Microscopy (TMAFM) in combination with measurements of ferrous iron concentrations and pH of the incubating solutions.Observations of live bacteria-surface interactions exposed to aerobic conditions showed localized pitting on Fe3+ oxyhydroxide coated quartz surfaces within 72 h of incubation. These pits corresponded directly to sites of bacterial surface adhesion and the extent of pitting was accompanied by the accumulation of ferrous iron to low but steady-state concentrations. Localized pitting was not observed on any Al3+ oxyhydroxide coated surfaces. In contrast, iron coated surfaces exposed to bacteria under anaerobic conditions revealed progressive, nonlocalized Fe loss over 96 h. This correlated with a temporal increase in ferrous iron concentrations in the bacteria-exposed solutions compared to the abiotic controls.Aqueous chemical measurements combined with the Fluid TMAFM observations indicate biologically-catalyzed iron reduction under both aerobic and anaerobic incubation. The pitting mechanism observed under aerobic conditions is proposed to result from a redox reaction at the bacteria-iron interface followed by the reoxidation of Fe2+ onto the surface. The evidence suggests that bacteria under anaerobic conditions maximize rates of dissimilatory reduction by remaining passively mobile on the surface. The weaker bacterial adhesion under anaerobic conditions enhances opportunities for bacteria-iron mineral surface contact. These findings may improve our understanding of relationships between the redox environment and bacterial mobility in the subsurface.